PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS GOOGLE SITES BERORIENTASI MODEL PEMBELAJARAN FIVES UNTUK MENINGKATKAN MOTIVASI DAN KEMAMPUAN NUMERASI PESERTA DIDIK KELAS V SD - Ning Listiarini, Dian; Rasmitadila; Dewi Nirmala, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low numeracy skills of students at the Elementary School level, based on the results of the National Assessment, show that around 38% of fifth grade elementary school students are in the